Map of Scientific Research on Circular Economy with Origin in Ecuador - Erazo-Rivera, Renato Patricio (2024)
The recovery of solid waste for conversion into resources for the future plays an important role in achieving environmental sustainability and developing circular economy models. For this reason, there has been an increase in scientific research at the international level, Ecuador being no exception.  Based on the bibliometric analysis, articles from the Scopus database were reviewed to conceptualize the central body of the research. As a result, some topics were identified such as: electronic waste, sustainable development, plastic waste, life cycle assessment, ecological impacts and industrial symbiosis. Nevertheless, the fact that Ecuador was the first country in Latin America to present the Circular Economy White Paper, it is evident that there are still insufficient studies originating in Ecuadorian institutions, thus accentuating the technical gap regarding its implication in Ecuador’s productive processes.